Spatial Expansion of Human Settlement during the Longshan Period (~4.5–~3.9 ka BP) and Its Hydroclimatic Contexts in the Lower Yellow River Floodplain, Eastern China - Kaifeng Li; Wenhua Gao; Li Wu; Hainan Hu; Panpan Gong; Suyuan Li; Rui Jin; Yi Si (Land, 2021)
Obvious spatial expansion of human settlement occurred in the lower Yellow River floodplain during the Longshan period, but the external factors driving this expansion remain unclear. In this study, we first delineated the hydroclimatic changes at both regional and local scales within and around the lower Yellow River floodplain and then examined the relationships of human settlements with hydroclimatic settings between the pre-Longshan and Longshan periods. The results indicate that the site distribution, site density and hydroclimatic conditions exhibited significant shifts during the pre-Longshan and Longshan periods. In the pre-Longshan period, the intense East Asian summer monsoon and abundant monsoon-related precipitation caused widespread development of lakes and marshes in the lower Yellow River floodplain. As a result, the circumjacent highlands of the lower Yellow River floodplain contained concentrated human settlements. However, the persistent weakening of the East Asian summer monsoon and consequent precipitation decline, in conjunction with accelerated soil erosion due to decreasing forest vegetation and strengthening of human activities on the upstream Loess Plateau in the Longshan period, are likely to have jointly caused both shrinking and faster filling of preexisting lakes and marshes. Subsequently, a large area of arable land had been created in the lower Yellow River floodplain and thus was occupied by locally rapid increasing population, resulting in the notable spatial expansion of human settlements during the Longshan period.